Alasan yang Meringankan Hukuman Terhadap Justice Collaborator Dalam Mengungkap Suatu Tindak Pidana - Ocktresia. M. Sihite; Madiasa Ablisar; Mahmud Mulyadi; Marlina Marlina (Universitas Sumatera Utara, 2019)
Abstract. Background is setting about justice collaborator or a witness who cooperated in the proof of the law in Indonesia is a new thing, the term justice collaborator is known from the revolutionary efforts in the practice of criminal law enforcement, which owns the impact of the development mode of the crime in Indonesia. Its existence then get attention and then began to set in positive law. The research method used in this thesis is a normative legal research methods. Method of normative legal research is research which refers to the legal norms contained in legislation and judicial decisions. The conclusion of this thesis conception of justice collaborator in the justice system in Indonesia is a collaborator Justice can also be called as whistleblowers or whistle blowers who want to cooperate with law enforcement officials or partisipant whistleblower. Implementation of the system of criminal justice collaborator in Indonesia. Strengthening the instruments Whistle Blower and Justice Collaborator in the prevention and eradication of corruption is reinforced by Presidential Instruction No. 2 of 2014 on Action Prevention and Combating of Corruption of 2014, which mandates the Ministry / Agency, including the Ministry of Justice and Human Rights to at least provide a Standard Operating Procedure (SOP) which guarantees the protection and confidentiality. The reason that commute to justice collaborator in uncovering a crime that lack of support, especially the protection of the respect / appreciation sufficient for them, often not comparable with the importance of the information they disclose to law enforcement and the public interest. Keywords: justice collaborator, crime, actors, punishment